Aerodynamic Characteristic Of Vortex Bladeless Wind Turbine: A Short Review - Sabab, Muhammad Wafi; Mohd, Sofian (Research Progress in Mechanical and Manufacturing Engineering, 2021)
The production of electricity from wind generators have been widely used. It attracts a great share in the electrical power production market worldwide as wind turbine industry. There are few types of wind turbine which is Horizontal Axis Wind Turbine (HAWT), Vertical Axis Wind Turbine (VAWT), and vortex bladeless wind turbine. The vortex bladeless wind turbine is a vortex-induced vibration resonant wind turbine which considered as most environmentally friendly wind turbine. As for a start-up in Spain, Vortex Bladeless Ltd have been experimenting on how to bring the maximum efficiency of power conversion of the bladeless wind turbine as it is still not fully done with zero commercialization. Hence, the purpose of the study is to analyze few shape and configurations of the vortex bladeless wind turbine using computational fluid dynamics (CFD) and next identifying the significance of aerodynamic characteristic on the bladeless wind turbine as to determine the optimum shape of the vortex bladeless wind turbine. The method used in this study is run the 2D and 3D model of vortex bladeless wind turbine that designed from SolidWorks in CFD simulation using Ansys-Fluent software. The two main design of 3D model vortex bladeless wind turbine are varied into five different configuration each. The data from simulation is interpreted into several ways which one of it from vertex average of velocity and graph extracted from Fast Fourier Transform (FFT) process. The most optimum configuration of the vortex bladeless wind turbine was obtained which is Design A4 by having the highest value fv/fn equal to 0.62, as well as the aerodynamic characteristic and parameters that affect the selection of the configuration. Suggestion for future work is to detail the mass portion of the shape of the bladeless wind turbine and use enhanced way in obtaining data from FFT.